The Implementation of the Quarantine Management Philosophy in Tahfiz and Boarding School to Enhance Enrollment Interest at MAN Insan Cendekia Paser - Arbain, Arbain; Wardhana, Kautsar Eka (P3KM Politeknik Pertanian Negeri Samarinda, 2023)
This research aims to examine the implementation of the philosophy of tahfiz quarantine and boarding school management in increasing enrollment interest at Insan Cendekia Paser Islamic High School. The study employs a qualitative method with a descriptive approach. Data are collected through observation, interviews, and documentation. The results indicate that the implementation of the philosophy of tahfiz quarantine and boarding school management at Insan Cendekia Paser Islamic High School has had a positive impact on increasing enrollment interest, as evidenced by the growing number of applicants each year. Student registration for the first time in 2015 was 150 students, until 2023 there will be 371 students interested in registering. This research took data from the deputy head of the school for public relations and student affairs, parents and students when re-registering in 2023. The research shows that among parents and students interested in entering MAN Insan Scholar Paser is the existence of a dormitory system and tahfiz activities as part of the superior program MAN Paser Scholar Person. The philosophy emphasizes the importance of character development, morality, and knowledge. Tahfiz quarantine and boarding school also provide a unique and engaging experience for students, making them more interested in studying at Insan Cendekia Paser Islamic High School. Research topics include parents of students, incoming students, students who are undergoing or who have been quarantined in Tahfiz, as well as students who live in the MAN Insan Scholar Paser Dormitory. This diversity of research topics provides a more comprehensive picture of the impact of implementing management principles. Information collection was carried out through interviews, observation and document analysis. Based on these findings, it can be concluded that the implementation of tahfiz quarantine and boarding school management philosophy can be considered a contributing factor in enhancing enrollment interest at MAN Insan Cendekia Paser.